Identification of B- and T-Cell Epitopes within the Fibronectin-Binding Domain of the SfbI Protein of Streptococcus pyogenes - Schulze, Kai (Infect Immun, 2003)
The fibronectin-binding repeats of the SfbI protein of Streptococcus pyogenes constitute the minimal domain able to confer protection against lethal infection. We investigated the presence of B- and T-cell epitopes within this region in congenic mice. One linear B-cell epitope was recognized by BALB/b and BALB/k mice, whereas two epitopes were found in BALB/c animals. A unique T-cell epitope was recognized by all three mouse strains. All identified epitopes clustered in a 30-amino-acid fragment. These results suggest that this polypeptide may be suitable for incorporation into a polyepitope-based vaccine formulation against S. pyogenes.